In vivo two-photon imaging reveals a role of progesterone in reducing axonal dieback after spinal cord injury in mice. (April 2017) - Yang, Zhijie; Xie, Wenguang; Ju, Furong; khan, Akbar; Zhang, Shengxiang
Abstract: Progesterone (PG) as a neuroprotective reagent has been used for the treatment of spinal cord injury (SCI) in experimental animal models. However, its effect and mechanism on axonal dieback at the early stage of SCI remain unclear. Here, we investigate the dynamics of injured axons and the effect of PG on the axonal dieback, glial response, and behavioral recovery in a mouse model of SCI. Two-photon intravital imaging combined with a simplified imaging window chamber were used to image axons in hemisected spinal cords over a period of 3 days. Repeated imaging showed that axonal dieback distance in mice treated with PG after SCI was significantly reduced than that in mice treated with vehicle after SCI (P < 0.05) at the time point of 24 h, 48 h, and 72 h after SCI. The densities of astrocytes and microglia in the SCI-vehicle treated group were significantly higher than those in mice treated with PG after SCI (P < 0.05). Real time polymerase chain reaction assay indicated that administration of PG after SCI down-regulated the expression of pro-inflammatory cytokines MCP-1, NOS2, and IL-1β (P < 0.05). PG treatment also improved the behavioral performance post injury. These findings suggested that PG exerted a neuroprotective effect by attenuating axonal dieback, reducing the accumulation of astrocytes and microglia and inhibiting the release of pro-inflammatory cytokines. Highlights: PG reduced axonal dieback distance in the acute stage of SCI. PG attenuated the accumulation of astrocytes and microglia after SCI. PG down-regulated the expression of pro-inflammatory cytokines after SCI. PG improved the functional recovery in the chronic stage of SCI.